Pharmacological profile of ficus thonningii: a review (World Journal of Current Medical and Pharmaceutical Research, 2021)
Ficus thonningii is an African ethnomedicine plant used to treat a number of diseases. The nutritional, phytochemical, and pharmacological aspects of F. thonningii in relation to its therapeutic purposes are numerous. Ficus thonningii contains alkaloids, terpenoids, flavonoids, tannins, active proteins, and active proteins. Continue to identify, isolate, and quantify the active ingredients, as well as their medicinal purposes. Chronic toxicity, toxicology, antineoplastic effects, acute toxicity, hypoglycemic effects, antidiarrheal effects, analgesic effects, anti-inflammatory effects, antioxidants, antifungal activity, antimicrobial effects, antiprotozoal properties etc.